Caracterización química y mineralógica usando EDS en arcillas naturales y activadas como elementos adsorbentes de contaminantes - Cando Pichucho, Guido Fabricio (2019)
The objective of this research was to determine the physical-chemical characteristics of samples of natural and activated clays from the Province of Pastaza. We worked with natural clays and activated in acid and basic medium. The clays were characterized by scanning electron microscopy, Fluorescence of X-rays and diffuse reflectance. After the acid treatment the size of the aggregates decreases, and its porosity increases, in the micrographs of clays can be identified that the average size of the aggregates is 142.02 μm, compared to clays activated with a base, where it can not be differentiate the size due to an amorphous structure. Natural gray clays and yellow have a higher percentage of SiO2 than red clay. While the contents of Al2O3 and Fe2O3 are higher in Red clay. In the signatures of the 15 clays, different functional groups were found, such as the FeO and its variations (Fe2+, Fe3+, FeOH). In all the cases studied, the signal intensity associated with the functional group FeO was high in brown clays and red, while the intensity of the signal associated with Fe2O 3 was high only in the Red clay. What suggests the presence of a significant amount of oxide of Iron in red clay and coffee? The intensity of the signal associated with the functional group AlOH was high in red and white clay activated with acid. Suggesting that you Clays have significant amounts of kaolinite. These results coincide qualitatively with the results of the FRX analysis, which suggest that clay richer in compounds with aluminum (kaolin) and iron is red clay, however, white clay also exhibits a content important of compounds with ALOH associated with kaolin